Microalgae: A Treasure Trove of Anticancer Nutraceuticals and Promising Therapeutic Mechanisms - Sajjad Masoumi; Maryam Zokaei; Ardavan Ahmadvand; Nogol Ghalamkarpour; Naghmeh Asadimanesh; Armin Azarimatin; Khashayar Fattah; Zahra Payandeh; Masoumeh Rostami; Afsaneh Farjami; Rajan Kumar Pandey; Mohsen Nabi-Afjadi (Advanced Biomedical Research)
With cancer remaining a global health concern, the need for new and effective preventive and treatment methods is paramount. Microalgae have emerged as a potential source of anticancer nutraceuticals. Our research indicates that substances produced from microalgae, such as carotenoids, polyunsaturated fatty acids, phycocyanin, and polysaccharides, have shown anticancer effects in both laboratory and human investigations. Carotenoids, including astaxanthin, have shown the ability to hinder the development of tumors and trigger programmed cell death (apoptosis) in several types of cancer cells. Moreover, studies have shown that phycocyanin, a blue pigment present in some species of microalgae, has properties that help reduce inflammation and combat cancer. Potential future research directions include expanding the scope of the study to encompass a diverse range of microalgae species, identifying other compounds with anticancer properties, and investigating the mechanisms by which chemicals derived from microalgae function in the treatment and prevention of cancer. Moreover, it is important to establish scalable and sustainable procedures for the industrial production of compounds derived from microalgae. In conclusion, our evaluation reveals that microalgae have enormous potential as a source of anticancer nutraceuticals, containing a variety of bioactive substances that could eventually lead to the development of novel and effective cancer prevention and treatment methods. To realize the maximum potential of chemicals derived from microalgae, it is necessary to develop a sustainable and environmentally benign industry and to continue research in this area.